Cardiovascular Safety of Dipeptidyl-Peptidase IV Inhibitors: A Meta-Analysis of Placebo-Controlled Randomized Trials - Elgendy, Islam Y.; Mahmoud, Ahmed N.; Barakat, Amr F.; Elgendy, Akram Y.; Saad, Marwan; Abuzaid, Ahmed; Wayangankar, Siddarth A.; Bavry, Anthony A. (American journal of cardiovascular drugs : drugs, devices, and other interventions, 2017)
Background Large randomized trials have shown conflicting evidence regarding the cardiovascular safety of dipeptidyl-peptidase 4 (DPP-4) inhibitors. Systematic reviews have been limited by incomplete data and inclusion of observational studies. This study aimed to systematically evaluate the cardiovascular safety of DPP-4 inhibitors in patients with type 2 diabetes. Methods Electronic databases were searched for randomized trials that compared DPP-4 inhibitors versus placebo and reported cardiovascular outcomes. The main outcome assessed in this analysis was heart failure. Other outcomes included all-cause mortality, cardiovascular mortality, myocardial infarction, and ischemic stroke. Summary odds ratios (ORs) were primarily constructed using Peto’s model. Results A total of 90 trials with 66,730 patients were included. Compared with placebo, DPP-4 inhibitors were associated with a non-significant increased risk of heart failure [OR 1.11, 95% confidence interval (CI) 0.99–1.25, P = 0.07] at a mean of 108 weeks. The risk of all-cause mortality (OR 1.03, 95% CI 0.94–1.12, P = 0.53), cardiovascular mortality (OR 1.02, 95% CI 0.92–1.14, P = 0.72), myocardial infarction (OR 0.98, 95% CI 0.88–1.09, P = 0.69), and ischemic stroke (OR 0.99, 95% CI 0.85–1.15, P = 0.92) was similar between both groups. Conclusion In patients with type 2 diabetes, the safety profile of DPP-4 inhibitors is similar to placebo. As a class, there is only weak evidence for an increased risk of heart failure.